2017
DOI: 10.1108/md-04-2016-0213
|View full text |Cite
|
Sign up to set email alerts
|

Open innovation in the food and beverage industry

Abstract: Purpose: The aim of this paper is to extend our knowledge into the relationship between open innovation and firm innovative performance. Specifically, we aim to determine whether the benefits of OI practices are different for Food and Beverage (FnB) firms as compared to those of other sectors. The FnB industry is relevant in terms of employment GDP generation in the UE, characterised by high integration and low-tech intensity. Methodology: In order to achieve our goal and obtain robust results, we consider fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(70 citation statements)
references
References 77 publications
2
60
1
3
Order By: Relevance
“…The findings of this present study can be considered as one of the few external sources of open innovation, as suggested by Bayona-Saez et al [111] for marketing managers of middle-priced restaurants. The research clearly shows that customer expectations for middle-priced restaurant services are very similar to expectations for luxury restaurants and are associated more to intangible aspects of services encountered, such as appropriate behavior manners both from personnel and other customers side, privacy seeking and less to the physical dimension of restaurant services.…”
Section: Discussion: Social Servicescape Factors and Open Innovation In Restaurant Servicessupporting
confidence: 70%
“…The findings of this present study can be considered as one of the few external sources of open innovation, as suggested by Bayona-Saez et al [111] for marketing managers of middle-priced restaurants. The research clearly shows that customer expectations for middle-priced restaurant services are very similar to expectations for luxury restaurants and are associated more to intangible aspects of services encountered, such as appropriate behavior manners both from personnel and other customers side, privacy seeking and less to the physical dimension of restaurant services.…”
Section: Discussion: Social Servicescape Factors and Open Innovation In Restaurant Servicessupporting
confidence: 70%
“…Different effects of innovation strategies on process innovation can be found in the literature (Greco et al, 2015;Bayona-Saez et al, 2017). In low technology intensity sectors, external innovation strategy positively affects process innovation (Cruz-C azares et al, 2010).…”
Section: Innovation Strategy and Process Innovationmentioning
confidence: 99%
“…Furthermore, open innovation affects economic dynamics on a more macroscopic level: not only through the relationship between open innovation and closed innovation, but also through the dynamics of open innovation and social innovation [37]. In other words, through several feedback loops, such as the open innovation of a knowledge city and the open innovation of a national innovation system, powerful open innovation reinforcement loops exist on the macro level [38]. Also, the development and application of various business models that connect the firms and the market together with open innovation have to be newly understood and explained through a reinforcement of open innovation or balanced loops [39].…”
Section: Discussionmentioning
confidence: 99%